San Francisco Provincia de Córdoba . Provincia de Santa Fe (EJERCITO ARGENTINO, 1997)
1 carta satelital (90x50 cm.) ; 1 : 250 000. San Francisco 3163-IV. Orbita 227082: 25 de febrero 1994 ; Orbita 228081: 12 de enero de 1993 ; Orbita 228082: 12 de enero de 1993.